Job Demands and Job Resources of Academics in Higher Education - Naidoo-Chetty, Mineshree; du Plessis, Marieta (Frontiers in Psychology, 2021)
Too many job demands and not enough job resources can negatively influence the well-being of employees. Currently, limited information exists surrounding the job demands and resources as experienced by academic employees in the higher education sector. Therefore, the aim of this study was to identify the job demands and job resources experienced by academic employees using qualitative methods. Semi-structured interviews were conducted with 23 academic employees, using an Interpretative Phenomenological Approach. Thematic analysis, specifically template analysis was used to categorize the themes. Job demands were divided into three categories: quantitative (publication pressure, overburdened with the load, and competing time demands), qualitative (work/home balance, complexity of student support, organizational politics, and lack of mental health support) and organizational demands (using technology-mediated learning and lack of structural resources). Job resources were organized into two categories: organizational (social support) and personal resources (autonomy, meaningful work, and personal support). Participant experiences are highlighted to provide a better understanding of the job demands and job resources encountered. The framework of job demands and job resources gleaned from the study could be used for further research to manage and monitor motivational processes for academic staff, and to reduce strain due to high job demands.